SIRIM Berhad Tower Shah Alam (Block 5: Centre of the Customer Service) Selangor Darul Ehsan / Nur Fazira Abdullah ... [et al.] - Abdullah, Nur Fazira; Mat Muni, Nurul Shafikah; Abdul Rahman, Amir Faris; Amat Rosman, Aiman Syahmi (2018)
A purpose-built 14-storey office building identified as a SIRIM Berhad Tower Shah Alam (Block 5: Centre of the Customer Service) and use for the office. The lobby in this building is at ground floor and the largest space in the building is auditorium that is located at first floor. As for the VIP room, the president of SIRIM Berhad Tower is at 4th floor. The rest is for the office use. SIRIM Berhad Tower Shah Alam (Block 5: Centre of the Customer Service) is built as a premier industrial research and technology organization in Malaysia, wholly-owned by the Ministry of Finance Incorporated. With over forty years of experience and expertise, SIRIM is mandated as the machinery for research and technology development, and the national champion of quality. SIRIM Berhad Tower is located at 1, Persiaran Dato’ Menteri, PO. BOX 7035, Section 2, 40700 Shah Alam, Selangor, Malaysia. The building was constructed in early of the year 1994 and complete in 1996 which is in two years and they already operate about 22 years until now. So far, for this building, there are no renovation work or refurbishment because the building is well maintained based on our impression on our first day went there. This building is surround with many facilities which is CoopMart, field, outdoor fitness equipment and multifunction hall. The major maintenance in this building is In-House department because they have their own specialities and expertise that can repair their own building and a minor maintenance is Out-Source such as security, cleaning, waste disposal and other thing that is not their expert when it comes to major defect.